A revolução ecumênica: do proselitismo ao compromisso de transformação social - Souza, Darli Alves de (2021)
This thesis aims to analyze the religious phenomenon that transformed the ecumenical movement in Latin America. The term chosen to name this phenomenon is ecumenical revolution. It took place in Latin America, between the 1950s and the 1970s. During the period under analysis, there was a radical change of reference in the ecumenical movement. Until the period prior to the delimitation chosen, it had an emphasis on missionary-evangelistic action. In the analyzed period, the theme of engagement in social transformation becomes the key element that guides the new direction of this movement. The scenario of the proposed period is marked by technological, political and economic changes. The industrialization process changes people's daily lives. In addition, there is a transition, in the political sphere, from populism to the bloody dictatorships guided by the United States of America. In the economy, the “economic miracle” is obtained through a high social cost and the granting of large loans and financing to Latin American countries. Furthermore, in the religious sphere, Protestantism had an unstable attitude and oscillated between omission, collaboration and resistance to the implanted dictatorships. There were also internal conflicts. The ecumenical revolution was possible because of the confluence of favorable factors in the Latin American context. Added to this, there is the performance of revolutionary ecumenical intellectuals, with the support of ecumenical cooperation that finances the organizations led by this group. Without this set of factors, the trajectory of the ecumenical movement would have other shapes. Methodological elements of bibliographic analysis were used for the documents of the time - primary and secondary sources -, websites, publications in general and interviews with leaders who worked during the period under analysis. The results obtained indicate that the revolution mentioned, through the set of factors above, was a crystalline reality that changed the course of the Latin American ecumenical movement